Observations and preliminary science results from the first 100 sols of MSL Rover Environmental Monitoring Station ground temperature sensor measurements at Gale Crater. Issue 4 (10th April 2014) - Hamilton, Victoria E.; Vasavada, Ashwin R.; Sebastián, Eduardo; de la Torre Juárez, Manuel; Ramos, Miguel; Armiens, Carlos; Arvidson, Raymond E.; Carrasco, Isaías; Christensen, Philip R.; De Pablo, Miguel A.; Goetz, Walter; Gómez‐Elvira, Javier; et al.
Abstract We describe preliminary results from the first 100 sols of ground temperature measurements along the Mars Science Laboratory's traverse from Bradbury Landing to Rocknest in Gale. The ground temperature data show long‐term increases in mean temperature that are consistent with seasonal evolution. Deviations from expected temperature trends within the diurnal cycle are observed and may be attributed to rover and environmental effects. Fits to measured diurnal temperature amplitudes using a thermal model suggest that the observed surfaces have thermal inertias in the range of 265–375 J m−2 K−1 s−1/2, which are within the range of values determined from orbital measurements and are consistent with the inertias predicted from the observed particle sizes on the uppermost surface near the rover. Ground temperatures at Gale Crater appear to warm earlier and cool later than predicted by the model, suggesting that there are multiple unaccounted for physical conditions or processes in our models. Where the Mars Science Laboratory (MSL) descent engines removed a mobile layer of dust and fine sediments from over rockier material, the diurnal temperature profile is closer to that expected for a homogeneous surface, suggesting that the mobile materials on the uppermost surface may be partially responsible for the mismatch between observed temperatures and those predicted for materials having a single thermal inertia. Models of local stratigraphy also implicate thermophysical heterogeneity at the uppermost surface as a potential contributor to the observed diurnal temperature cycle.